Discrete host-parasitoid models with Alleeeffects and age structure in the host - Sophia R.-J. Jang (Mathematical Biosciences and Engineering)
We study a stage-structured single species population model withAllee effects. The asymptotic dynamics of the model depend on themaximal growth rate of the population as well as on its initialpopulation size. We also investigate two models of host-parasitoidinteraction with stage-structure and Allee effects in the host.The parasitoid population may drive the host population toextinction in both models even if the initial host population isbeyond the Allee threshold.